Profile of the use of the drug domperidone in elderly patients admitted to a university hospital (Research, Society and Development, 2023)
Objective: To evaluate the profile of the use of the drug Domperidone in elderly patients admitted to the University Hospital Prof. Alberto Antunes – HUPAA. Methodology: Quantitative, descriptive and cross-sectional study of the medical records/prescriptions of elderly patients hospitalized in the medical, oncological and surgical clinics of the HUPAA in the year 2020 who used the drug domperidone in the form of a tablet, the information was collected through the Electronic System of the Hospital, recorded in a specific form created for the record of data collection. Data were tabulated in the Excel® software program (Office 2010) and descriptive statistical analysis was performed using the Statistical Package for the Social Sciences (SPSS) 17.0. Results: In this study, 23 (45%) patients were included because they were ≥60 years old, the median age was 66 years, interquartile range (IQR) 8 and 78% were female. The Internal Medicine represented 56% of the elderly, the reason for the most described indication was a feeling of fullness, nausea and abdominal distension, the electrocardiogram was performed in only one patient, a dose of ≤30 mg/day (96%) of the drug was predominant. The duration of treatment of one week followed the indication for vomiting/nausea (74%), and among the drugs that prolong or may prolong the QT interval co-administered were omeprazole (87%) and ondansetron (48%), and the drugs combined per patient had a median of 3.0 (IQR 1.0). Conclusion: This study aims to contribute to the decision-making of health professionals and the safety and health of the elderly in the hospital environment.